Bark Effects on Stemflow Chemistry in a Japanese Temperate Forest I. The Role of Bark Surface Morphology - Oka, Ayano; Takahashi, Junko; Endoh, Yoshikazu; Seino, Tatsuyuki (Frontiers in Forests and Global Change, 2021)
Stemflow plays role in the pathway of rainfall and mineral cycling through trees in the forest ecosystem. The effects of bark structure on the chemical composition of stemflow in temperate forests from seasonal and anatomical perspectives were examined with a focus on the diversity of bark morphology. Six species (four deciduous broadleaf trees and two evergreen coniferous trees) with different types of bark external morphology were examined for the chemical components of direct rainfall, throughfall, and stemflow at two sites in montane and a suburban area. The smooth-barked species contained more minerals rinsed from the stem surface, such as Cl-, in the stemflow, while rough-barked species contained more minerals leaching from the tree body, such as Ca2+. The results suggest that the dynamics of dry deposits in the forest are influenced by the surface structure of the bark. The exchange of dissolved minerals from the inside to the outside of the tree body was suggested to be related to the thickness of the bark surface and the external structure. These results indicate that the characteristics of the external bark structure and the tendency of chemical components in the stemflow are related and that the pattern of stemflow is an important factor in the mineral cycle between the tree and the external environment through the bark.